Disruptive innovation in traditional clusters: the case of the kerajet ceramic tile cluster in Spain (2019)
Academic literature has often emphasized how firms in regional clusters exploit both place-specific local resources and external, world-class knowledge to strengthen their competitiveness by expanding the influence of regional systems of innovation. Innovation based on more complex and disruptive technologies tends to also be based on more open systems that utilize the clusters’ external networks. However, most of the literature has associated clusters with incremental innovation. This paper will analyze the determinants of disruptive innovation development in traditional (low and medium tech) clusters caused by high-tech entrepreneurs. It will analyze the case of the development of breakthrough innovation, its diffusion in the Spanish ceramic tile cluster, and its consequent diffusion in the industry worldwide. It will examine how market demands, customer orientation, technology diffusion from other industries, industry competitiveness, as well as internal and external networking of clusters can facilitate the development of complex technology within a common set of social capital goals, cognitive schemes, and knowledge. The paper is based on a case study and field work carried out over10 years in the field in the Italian and Spanish tile ceramic clusters. The main contribution of this paper to technology strategy theory will be thorough the utilization of the disruptive technology paradigm in explaining industry changes and sustainability.